1992
DOI: 10.1161/01.str.23.9.1265
|View full text |Cite
|
Sign up to set email alerts
|

Low and high density lipoprotein metabolism in atherothrombotic brain infarction.

Abstract: Our study provides insights into the role of altered low and high density lipoprotein metabolism in the pathogenesis of carotid stenosis. The statistically significant association of serum lipoprotein metabolic rates with carotid stenosis, rather than their respective serum concentrations, implies that metabolic parameters may be more important in predicting stroke risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…Observational studies found an association between hypercholesterolaemia and carotid stenosis[2,3,4]. However, elevated plasma cholesterol has been inconsistently associated with brain infarction (BI)[5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies found an association between hypercholesterolaemia and carotid stenosis[2,3,4]. However, elevated plasma cholesterol has been inconsistently associated with brain infarction (BI)[5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…[24] show that the majority of the studies reviewed, namely, 23 of 26 assess ing lipid abnormalities in ABls, demonstrate a correlation between cholesterol and ABls, although techniques, crite ria and study design differed substantially. Whether the dynamic process of plaque formation at the carotid bifur cation is due to lipid or coagulation/plalelet aggregation defects, Grolta et al [25] reported a significant increase in carotid stenosis of 2:23% over 30 m on th s was associated with a significant increase in LD L. In addition, evaluation of the dynamic aspects of L D L and IID L metabolism by assessing in vivo metabolism o f autologously labelled lipoproteins demonstrated a slower catabolism of LD L and a faster one for I IDL, suggesting that increased resi dent lime in serum combined with enhanced catabolism of H D L is associated with ABls [26], In addition to metabolic parameters supporting the role o f impaired or abnormal cholesterol transport in ABls, altered gene function for proteins involved in cho lesterol metabolism may likely play an important role in determining ABI susceptibility. For example, in a study of gene polymorphism o f the major apoprotein of I IDL, Kasturi et al [27] reported on the occurrence of restric tion fragment length polymorphism (RFLP) of the tandemly arranged apoproteins of A l, ( 'III, and AIV on the long arm o f chromosome 11.…”
Section: Investigations On Abi: Multiple Factorsmentioning
confidence: 97%
“…A role of lipoprotein(a) (lp(a)) as an ischemic stroke biomarker and as a predictor of recurrence has also been suggested [122]. Studies have shown an inverse relationship between high-density lipoprotein cholesterol (HDLc) and ischemic stroke, particularly in atherothrombotic subtype [123,124], wherein low HDLc concentrations are associated with increased stroke severity and poor clinical outcome [42]. It is of interest to consider the values of HDLc, along with those of LDLc, in order to better predict the risk of stroke.…”
Section: Lipids and Lipoproteinsmentioning
confidence: 99%